Evaluating the Viability of Mobile Learning to Enhance Management Training - Iain Macdonald; Jason Chiu (The Canadian Network for Innovation in Education (CNIE), 2011)
A qualitative research project was conducted to test the viability of augmenting an e-learning program for workplace learners using mobile content delivered through smart phones. Ten learners taking a six week web-based e-learning course were given smart phones which enabled them to access approximately 70% of the course content, in addition to having access to the full course via a standard e-learning website. Mobile content was provided in a variety of forms, including text, audio and video files, a mobile multiple-choice quiz website, and links to streaming videos. Study participants who were regular users of mobile phones found the mobile learning materials to be user-friendly, offering increased convenience and flexibility. Use of the mobile content tended to increase as learners spent more time in their day away from locations where Internet-linked computers could be found. Video was found to be the most effective means of presenting content, followed by audio and text. The most promising role of mobile learning appears to be to augment rather than replace e-learning or blended learning.